A case of renal cell carcinoma with late recurrence in the bilateral hilar lymph nodes twenty years after surgery. (2022) - Sakurai, Yusuke; Matsuura, Hiroyuki; Oshima, Yuri; Hirai, Kaho; Tani, Eriko; Yoshimoto, Naoki; Minami, Kenichi; Wakasa, Kenichi; Hirashima, Tomonori
Abstract: Renal cell carcinoma (RCC) is a common malignancy with a high recurrence rate. However, brain and bilateral hilar lymph node (BHL) relapse is rare. A 65-year-old man with a chief complaint of hemosputum visited the primary care clinic. Computed tomography revealed BHL enlargement. Histopathological examination of biopsy specimens from the left lingular bronchus revealed RCC. This finding was similar to that of a left nephrectomy specimen of RCC observed 20 years ago. If patients have a medical history of RCC, physicians should consider the possibility of RCC recurrence, regardless of the number of years relapsed postoperatively.